The Social Network of High and Low Self- Monitors and it’s Impact on Organization’s Performance - Shaker, Fahim (Asian Business Review, 2014)
Self-monitoring as a personality attribute is given particular attention by researchers in order to understand employee performance and productivity in the organizational context. Numerous studies focused on the impact of self-monitoring from individual employee perspective with limited focus on the impact of the organization’s performance. However, to what extent employees with high versus low self- monitors contribute to the organization’s performance needs to be theoretically augmented. Therefore, relying on exploratory method of research, the paper tries to address the impact of high and low self-monitors on organization’s performance. In this perspective, how self-monitoring helps employees to structure a social network within organizational setting and eventually contribute to it’s success is discussed in this paper. The paper addresses the literature review of self-monitoring principles with special interest in its contribution towards organizational performance through previous research compilation within the field of sociology and organization psychology.JEL Classification Code:  M 12; M 14
Keywords: Self-Monitoring; Social Network; Organization; Performance